2006
DOI: 10.1001/jama.295.9.1033
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Status, Cardiovascular Risk, and Mortality in Older Adults

Abstract: Our data show an association between subclinical hyperthyroidism and development of atrial fibrillation but do not support the hypothesis that unrecognized subclinical hyperthyroidism or subclinical hypothyroidism is associated with other cardiovascular disorders or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
637
2
21

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(696 citation statements)
references
References 41 publications
36
637
2
21
Order By: Relevance
“…In the last few years, an increased number of prospective population-based cohort studies (100,138,140,158,(161)(162)(163)(164)(165)(166)(167) (A,A,A,A,A,A,A,A,A,B,B), have reported conflicting results on the potential relationship bet ween SH and cardiovascular disease and mortality. These discrepancies may be due to differences in the populations studied in terms of age, sex, race/ethnicity, life style, TSH cutoffs, differences in confounders adjustments, follow-up period, and selection bias (1) (D).…”
Section: Is Subclinical Hypothyroidism Associated To Cardiovascular Rmentioning
confidence: 99%
“…In the last few years, an increased number of prospective population-based cohort studies (100,138,140,158,(161)(162)(163)(164)(165)(166)(167) (A,A,A,A,A,A,A,A,A,B,B), have reported conflicting results on the potential relationship bet ween SH and cardiovascular disease and mortality. These discrepancies may be due to differences in the populations studied in terms of age, sex, race/ethnicity, life style, TSH cutoffs, differences in confounders adjustments, follow-up period, and selection bias (1) (D).…”
Section: Is Subclinical Hypothyroidism Associated To Cardiovascular Rmentioning
confidence: 99%
“…Investigators have previously developed prognostic indices within segments of the population (e.g., hospitalized elders 12 and nursing home residents 13 ). Others have examined the influence of specific comorbid diseases or functional status on mortality [14][15][16] , and one study examined the influence of laboratory measures of subclinical and clinical disease (e.g., fasting glucose level) on 5-year mortality. 17 Only one study examined the influence of several self-reported characteristics (e.g., age, comorbid conditions) on 4-year mortality in a nationally representative sample of US adults aged 50 and older.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence is also related to the degree of TSH suppression, with the age of the population studied being higher in subjects above the age of 60-70 years with low serum TSH levels (1). It is well recognized that the risk of adverse effects of SHyper is higher in elderly subjects because this disease could increase the risk of atrial fibrillation in the presence of subnormal (3) and undetectable serum TSH levels (3,4). Studies on the relationship between cardiovascular morbidity and mortality in exogenous SHyper (5)(6)(7)(8) induced by long-term treatment with L-T 4 have yielded conflicting results (9).…”
mentioning
confidence: 99%
“…Thus far, only a few studies have examined the risk of cardiovascular mortality in patients with endogenous SHyper (3,10,11); these were performed in middle-aged (11) and elderly subjects (3,10). Three studies have been performed in patients with co-morbidity associated with SHyper (12)(13)(14).…”
mentioning
confidence: 99%